STRATEGI INOVASI PRODUK DAN PEMASARAN DIGITAL PADA USAHA KULINER MIKRO PANCONG LUMER NIKMAT DENGAN MODAL TERBATAS - Muhammad Ananda Micola; Hamzahri Rasyid; Firmansyah Nefdi (Taksasila Edukasi Insani, 2026)
Micro culinary enterprises often struggle with limited capital, intense market competition, and rapidly changing consumer preferences, which hinder their ability to innovate and sustain business growth. This study addresses these core issues by examining how Pancong Lumer Nikmat, a micro-scale culinary venture, implements product innovation and digital marketing strategies despite financial constraints. The research aims to identify effective practices that enhance product appeal and increase market reach with minimal investment. A qualitative research approach was employed through direct observation, in-depth interviews with the business owner, and analysis of digital marketing content used on social media platforms. The findings reveal that product innovation focuses on developing unique flavor variations, adding contemporary toppings, and improving visual presentation to align with current food trends while maintaining affordable production costs. In terms of marketing, the strategic use of low-cost platforms such as Instagram, TikTok, and WhatsApp Business effectively increases brand visibility, strengthens customer engagement, and encourages organic promotion through visually appealing content. The study concludes that simple, cost-efficient product innovations combined with accessible digital marketing efforts can significantly improve consumer interest, repeat purchases, and brand identity formation. These strategies provide practical, scalable solutions for micro culinary businesses operating with limited resources. Keywords : consumer engagement, digital marketing, micro culinary business, product innovation, social media